BENEVOLENCE OF A LAW ENFORCEMENT OFFICER: THEORETICAL BASIS - Письменна, Олена (Modern engineering and innovative technologies, 2023)
The article examines integrity as a tool of law enforcement management and as a "new philosophy" for law enforcement officials in the fight against corruption. Virtue is clarified in a multifaceted approach in understanding the phenomenon of "virtue".